answersLogoWhite

0


Best Answer

Square Root

Geaux Tigers!

User Avatar

Wiki User

12y ago
This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: What does sqrt stand for?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

Is the square root of 38 rational or irrational?

Well, isn't that just a happy little question! The square root of 38 is actually an irrational number because it cannot be expressed as a simple fraction. It's like a beautiful little mystery in the world of numbers, just waiting to be explored and appreciated. Just remember, there's no mistakes in math, only happy little accidents!


What is the square root of 72 using radicals?

sqrt(72) = sqrt(36*2) = sqrt(36)*sqrt(2) = 6*sqrt(2).sqrt(72) = sqrt(36*2) = sqrt(36)*sqrt(2) = 6*sqrt(2).sqrt(72) = sqrt(36*2) = sqrt(36)*sqrt(2) = 6*sqrt(2).sqrt(72) = sqrt(36*2) = sqrt(36)*sqrt(2) = 6*sqrt(2).


What are the first 16 equations for the wheel of theodorus?

sqrt(1^2 + 1^2 ) = sqrt(2)sqrt(sqrt(2)^2 + 1^2 ) = sqrt(3)sqrt(sqrt(3)^2 + 1^2 ) = sqrt(4)sqrt(sqrt(4)^2 + 1^2 ) = sqrt(5)sqrt(sqrt(5)^2 + 1^2 ) = sqrt(6)sqrt(sqrt(6)^2 + 1^2 ) = sqrt(7)sqrt(sqrt(7)^2 + 1^2 ) = sqrt(8)sqrt(sqrt(8)^2 + 1^2 ) = sqrt(9)sqrt(sqrt(9)^2 + 1^2 ) = sqrt(10)sqrt(sqrt(10)^2 + 1^2 ) = sqrt(11)sqrt(sqrt(11)^2 + 1^2 ) = sqrt(12)sqrt(sqrt(12)^2 + 1^2 ) = sqrt(13)sqrt(sqrt(13)^2 + 1^2 ) = sqrt(14)sqrt(sqrt(14)^2 + 1^2 ) = sqrt(15)sqrt(sqrt(15)^2 + 1^2 ) = sqrt(16)sqrt(sqrt(16)^2 + 1^2 ) = sqrt(17)


What is the simplest square radical form for 50 and 3 square root of 8?

sqrt(50) = sqrt(25*2) = sqrt(25)*sqrt(2) = 5*sqrt(2)3*sqrt(8) = 3*sqrt(4*2) = 3*sqrt(4)*sqrt(2) = 3*2*sqrt(2) = 6*sqrt(2).sqrt(50) = sqrt(25*2) = sqrt(25)*sqrt(2) = 5*sqrt(2)3*sqrt(8) = 3*sqrt(4*2) = 3*sqrt(4)*sqrt(2) = 3*2*sqrt(2) = 6*sqrt(2).sqrt(50) = sqrt(25*2) = sqrt(25)*sqrt(2) = 5*sqrt(2)3*sqrt(8) = 3*sqrt(4*2) = 3*sqrt(4)*sqrt(2) = 3*2*sqrt(2) = 6*sqrt(2).sqrt(50) = sqrt(25*2) = sqrt(25)*sqrt(2) = 5*sqrt(2)3*sqrt(8) = 3*sqrt(4*2) = 3*sqrt(4)*sqrt(2) = 3*2*sqrt(2) = 6*sqrt(2).


What is the square root of A squared B plus the square root of A B squared divided by the square root of AB?

The question is ambiguous because it could refer to [sqrt(A2B) + sqrt(AB2)]/sqrt(AB) = [A*sqrt(B) + B*sqrt(A)]/[sqrt(A)*sqrt(B)] = A/sqrt(A) + B/sqrt(B) = sqrt(A) + sqrt(B) or sqrt(A2B) + sqrt(AB2)/sqrt(AB) = A*sqrt(B) + B*sqrt(A)/[sqrt(A)*sqrt(B)] = A*sqrt(B) + B/sqrt(B) = A*sqrt(B) + sqrt(B) = sqrt(B)*(1 + A)


What is the square root of a squared plus a squared equal?

sqrt(a2 + a2) = sqrt(2a2) = sqrt(2)*sqrt(a2) = sqrt(2)*asqrt(a2 + a2) = sqrt(2a2) = sqrt(2)*sqrt(a2) = sqrt(2)*asqrt(a2 + a2) = sqrt(2a2) = sqrt(2)*sqrt(a2) = sqrt(2)*asqrt(a2 + a2) = sqrt(2a2) = sqrt(2)*sqrt(a2) = sqrt(2)*a


What is 12 root 6 minus 12 root 12?

12 sqrt(6)-12sqrt(12) = 12 [sqrt(6)-sqrt(12)] sqrt(6)=sqrt(2x3) = sqrt(2) x sqrt(3) sqrt(12)=sqrt(22x3) = sqrt(22) x sqrt(3) = 2 sqrt(3) sqrt(6) - sqrt(12) = sqrt(2) x sqrt(3) - 2 sqrt(3) = sqrt(3) [sqrt(2)-2] So 12 sqrt(6)-12sqrt(12) = 12 sqrt(3) [sqrt(2)-2]


What is the square root of 80 over 45?

sqrt(80/45) = sqrt(16/9) = sqrt(16)/sqrt(9) = 4/3 sqrt(80/45) = sqrt(16/9) = sqrt(16)/sqrt(9) = 4/3 sqrt(80/45) = sqrt(16/9) = sqrt(16)/sqrt(9) = 4/3 sqrt(80/45) = sqrt(16/9) = sqrt(16)/sqrt(9) = 4/3


What is the square root of 12 times 2 square root 18 Times Square root 24?

sqrt(12)*2*sqrt(18)*sqrt(24) = sqrt(4*3)*2*sqrt(2*9)*sqrt(4*2*3) = sqrt(4)*sqrt(3)*2*sqrt(2)*sqrt(9)*sqrt(4)*sqrt(2)*sqrt(3) = 2*sqrt(3)*2*sqrt(2)*3*2*sqrt(2)*sqrt(3) = 24*sqrt(2)*sqrt(2)*sqrt(3)*sqrt(3) = 24*2*3 = 144


What are the quartic roots of zero plus 16i?

2*sqrt(0.5 + 0.25*sqrt(2)) + 2i*sqrt(0.5 - 0.25*sqrt(2)) -2*sqrt(0.5 - 0.25*sqrt(2)) + 2i*sqrt(0.5 + 0.25*sqrt(2)) -2*sqrt(0.5 + 0.25*sqrt(2)) - 2i*sqrt(0.5 - 0.25*sqrt(2)) 2*sqrt(0.5 - 0.25*sqrt(2)) - 2i*sqrt(0.5 + 0.25*sqrt(2))


Square root of 5 plus square root of 45?

sqrt(5) + sqrt(45) = sqrt(5) + sqrt(9*5) = sqrt(5) + sqrt(9)*sqrt(5) = sqrt(5) + 3*sqrt(5) = 4*sqrt(5)


What is radical 50 added to radical 8?

58